PERAN PERTAMBANGAN TERHADAP PENGEMBANGAN WILAYAH KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Wicaksono Tri Wuryanto; Kukuh Murtilaksono; Boedi Tjahjono (TATALOKA, 2018)
Tanggamus Regency has great mining resources potential of 152 831 928 tons. In order to contribute maximally to the local economy with well-preserved environment then the mining management should be wise. This research aims to analyze the role of the mining sector to the regional economy, analyzing the change of land use 2000-2015, as well as preparing the development plan direction of mining area in Tanggamus Regency. The methods used in this study include analysis of input output with aggregation and RAS, satellite image classification, and overlapping map techniques The mining sector has high value of forward linkages which demonstrate the ability of the mining sector in driving the sector in the future to grow, but the mining sector has low value of backward linkages, hence the driving force of the upstream sectors also low. Changes in land use in Tanggamus District from 2000 to 2015 are dynamics. The most changing land is agricultural land turned into developed land of 5 168 ha. At the mining site, the largest land use growth rate is developed land 265.74 ha/year. Identification result of area function utilization for mining activity shows that 6.03% of protected areas and 8.05% of cultivation areas utilized as mining area. Recommendations is the allocation of mining designated areas shall be directed to the area in the mining business permit of 20 773.82 ha.